2005
DOI: 10.1021/ac048469q
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dipeptide Isomers by Tandem Mass Spectrometry of Their Mono- versus Dilithiated Complexes

Abstract: The Li+ complexes of the isomeric dipeptide pairs PheGly/GlyPhe, PheAla/AlaPhe, and TrpAla/AlaTrp, namely, [Pep + Li]+, and of the corresponding lithium carboxylates, namely, [Pep - H + 2Li]+, are produced in the gas phase by desorption ionization, and their unimolecular chemistry is probed by tandem mass spectrometry experiments at various activation conditions. At low internal energies, monolithiated isomers dissociate to the same products, formed through a mixed anhydride intermediate in which the sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Mass spectrometry offers a convenient means for the isolation and the study of transient intermediates, if these are charged. Kenttämaa and coworkers [11][12][13][14][15][16] and, more recently, our group [17][18][19][20][21] have demonstrated that organic radicals containing inert charges, including alkali metal ion or quaternary pyridinium sites, primarily react at their radical centers. Such systems can therefore serve as templates for the investigation of the gas-phase chemistry of the corresponding neutral radicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry offers a convenient means for the isolation and the study of transient intermediates, if these are charged. Kenttämaa and coworkers [11][12][13][14][15][16] and, more recently, our group [17][18][19][20][21] have demonstrated that organic radicals containing inert charges, including alkali metal ion or quaternary pyridinium sites, primarily react at their radical centers. Such systems can therefore serve as templates for the investigation of the gas-phase chemistry of the corresponding neutral radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding dilithiated complexes, in which the -COOH termini are derivatized to COO Li + , are also investigated in order to determine the influence of salt bridges on radical reactivity. We recently showed that such radical ions can be generated by collisionally activated dissociation (CAD) of mono-or dilithiated dipeptides containing an aromatic amino acid residue at the position where the Gly • radical is to be introduced [20]. This method complements the synthetic procedure recently introduced by Siu et al [22], in which radical ions of complete peptides (they have one more H atom than the ␣-peptide radicals studied here) are prepared via gas-phase redox reactions from ternary complexes of a multiply charged transition metal ion, the peptide of interest and an auxiliary multidentate ligand [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, charge-driven fragmentation produces even-electron y-ions and odd-electron b-ions. (n-1)ϩ· ions produced by capture of low-energy electrons by multiply protonated molecules or by electron-transfer processes [1][2][3][4][5]9], hydrogen deficient radical anions [M Ϫ nH] (n-1)-· generated by electron detachment and photodetachment from multiply deprotonated molecules [10,11], peptides cationized on lithium [12], or transition metals [13][14][15][16], and M ϩ· peptide radical cations. [In this study, we used standard notation for molecular radical cations, M ϩ· , which implies that the molecule has a charge and one unpaired electron, and specified the initial location of the radical site, when possible].…”
mentioning
confidence: 99%
“…These data are consistent with the rearrangement mechanism proposed in Schemes 6 and 7. Consequently, these results show that ESI-MS/MS is a useful tool for isomeric differentiation through collisionally induced dissociation of the metal ion complexes [59,60]. …”
Section: Resultsmentioning
confidence: 79%